Effect Of Hormone Therapy On Fertility And Plasma Minerals Profile In Repeat Breeding Gir Cows - Parmar, Sachin V.; Patel, J.A.; Dhami , A.J. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
This study was carried out on 24 repeat breeding cows of Gir breed divided at random in to four groups, 6 animals in each. Animals of Group I were treated with single i/m injection of 0.02 mg buserelin acetate and Group II with single i/m injection of 1500 IU hCG immediately after natural breeding, while animals of Group III were administered with 500 mg of hydroxy-progesterone caproate on day 6 of natural breeding and those of Group IV bred without any treatment served as control. Blood plasma samples were collected on day 0 (oestrus) and then at weekly interval up to 6 weeks post-breeding/ treatment and were stored at -20°C. The first service conception rates obtained following 3 treatments were 50.00, 83.33 and 50.00 %, respectively, with an overall mean of 61.11 %. These were significantly higher (P<0.01) than that (16.66 %) obtained in untreated control group. The overall mean values of plasma calcium, inorganic phosphorus, Ca:P ratio and magnesium were 11.918±0.159 mg/dl, 8.193± 0.123 mg/dl, 1.516±0.032 and 1.818±0.028 mEq/ L without significant differences between weeks or between conceived and non-conceived groups, except magnesium, the level (mEq/L) of which in GnRH treated group (2.341±0.047) was significantly (P<0.05) higher than in hCG and Progesterone treated groups (1.731 ±0.023 and 1.620±0.021). The overall mean values of trace elements, viz., zinc, iron, copper and manganese were 1.549±0.008, 2.119±0.023, 0.779±0.005 and 0.090±0.001 ppm, respectively. The values of zinc and copper were significantly (P<0.05) higher in all three treated groups as compared to control group. The values were significantly higher (P<0.01) in conceived group as compared to non conceived group for all four elements, and varied significantly between weeks for copper and manganese. Overall, the hormonal therapy, especially hCG, was found highly effective in solving repeat breeding problem in Gir cows, though it did not influence the plasma mineral profile.